Therapeutic potential of miR-204-5p in intervertebral disc degeneration: targeting the SSRP1/NF-κB pathway to inhibit apoptosis - Chenhao Zhao; Qiuwei Li; Cailiang Shen (Journal of Orthopaedic Surgery and Research)
Abstract Background Intervertebral disc degeneration (IVDD) is a leading cause of lower back pain, imposing significant healthcare burdens globally. However, the molecular mechanisms underlying IVDD remain elusive, limiting effective therapeutic approaches. This study investigated the protective role of miR-204-5p in IVDD by targeting the Structure-specific recognition protein-1(SSRP1)/nuclear factor-kappa B (NF-κB) signaling pathway. Mendelian randomization (MR), experimental validation, and bioinformatics analysis were used. Methods We began with bidirectional MR analysis to explore the causal relationships between 40 microRNAs and IVDD, identifying miR-204-5p as negatively correlated with IVDD. Following this, in vitro experiments were conducted to examine the effects of miR-204-5p on lipopolysaccharide (LPS)-induced apoptosis in nucleus pulposus (NP) cells, with additional in vivo studies performed using rat models of disc degeneration. Finally, bioinformatics analysis was conducted using RNA-seq data from the GSE165722 dataset. Differential expression analysis was performed to compare SSRP1 expression between the control and degenerated tissue groups. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, and protein-protein interaction (PPI) network analyses were used to explore the biological pathways and regulatory networks. Results MR analysis identified miR-204-5p as being significantly protective against IVDD. The experimental results demonstrated that miR-204-5p reduced LPS-induced apoptosis in NP cells by downregulating SSRP1 expression and modulating the NF-κB pathway. Bioinformatics analysis further confirmed the differential expression of apoptosis-related genes, including SSRP1, BAX, and BCL2, between the control and degenerated tissues. Cluster analysis revealed distinct expression patterns of these genes, while correlation analysis showed strong interactions between SSRP1 and key extracellular matrix genes (COL2A1, ACAN) in degenerated tissues. Heatmaps and correlation matrices visualized these interactions, further supporting miR-204-5p’s protective role. Conclusion This study is the first to utilize a comprehensive approach, combining MR, experimental validation, and bioinformatics analysis to uncover the protective effects of miR-204-5p in IVDD by regulating the SSRP1/NF-κB pathway. These findings provide novel insights into IVDD pathogenesis and highlight miR-204-5p as a promising therapeutic target for future interventions.